Assessing the Information Technology Governance Trust Using Readiness and Usability Models: A Model Development Study - Resad, Setyadi; A'ang, Subiyakto; Aedah, Abd Rahman (2018)
Information Technology Governance (ITG) is important for schools and stakeholders to manage rights and responsibilities for decision-making processes. Institutional policies, systems, and users are the basic components of the proposed ITG model. The success of ITG is a primary concept in this topic. It occurs when users have a good level of trust in IT. The success of ITG implementation depends on the IT knowledge. There are several dimensions to measure in ITG implementation: readiness model, usability model, and input-process-output model. The researchers included level of trust into the input-process-output model, thus a new model of ITG implementation is obtained. Instead of using empirical evidence, this study develops the ITG implementation model by using theories from previous studies. The model is proposed and developed by incorporating the Nielsen usability model and the Parasuraman readiness model into the input-process-output model. The result is a model of IT governance trust that consists of 9 variables in 23 influential relationships. This study also shows coherent aspects of the process model, the causal model, and the questionnaire of each indicator.